Methyl 2-(5-bromo-3-methylsulfinyl-1-benzofuran-2-yl)acetate - Uk Lee; Byeng Wha Son; Pil Ja Seo; Hong Dae Choi (Acta Crystallographica Section E, 2008)
The title compound, C12H11BrO4S, was synthesized by the oxidation of methyl 2-(5-bromo-3-methylsulfanyl-1-benzofuran-2-yl)acetate with 3-chloroperoxybenzoic acid. The O atom and the methyl group of the methylsulfinyl substituent lie on opposite sides of the plane of the benzofuran ring system. The crystal structure is stabilized by C—H...π interactions, involving a methyl H atom and the benzene ring of a neighbouring molecule, and by weak intermolecular C—H...O hydrogen bonds.